M*A*S*H. Season four [videorecording (DVD)] - Gelbart, Larry; Alda, Alan, 1936-; Farrell, Mike; Morgan, Harry, 1915-2011; Swit, Loretta; Linville, Larry, 1939-2000; Burghoff, Gary; Farr, Jamie, 1934- (20th Century Fox Home Entertainment, 2003)
The adventures continue for the doctors and nurses of the 4077th unit during the Korean War.